Pengembangan Kinerja Guru Ditinjau dari Variabel Lingkungan Kerja dan Budaya Organisasi - Arifin, Samsul; Mardikaningsih, Rahayu (Jurnal Simki Pedagogia, 2021)
This explanatory research aims to determine the significance of the influence of work environment and organizational culture variables on teacher performance. The number of respondents involved were 51 teachers. The results of this study state that the work environment has a significant influence on teacher performance. Another independent variable, namely organizational culture also has a significant influence on teacher performance. The work environment becomes the independent variable that has the dominant influence. Simultaneously, the same thing also happened. The correlation between the independent and dependent variables is very strong.